2019
DOI: 10.1002/cap.10079
|View full text |Cite
|
Sign up to set email alerts
|

Successful Multidisciplinary Management of an Endodontic‐Periodontal Lesion Associated With a Palato‐Radicular Groove: A Case Report

Abstract: Introduction This case report describes the collaborative management of an extensive combined endodontic‐periodontal lesion related to a long palato‐radicular groove (PRG) on a maxillary lateral incisor. Cases with similar severity have been reported minimally in the endodontic journals but even less in the periodontal journals. This case report illustrates the result of multidisciplinary treatment of the combined lesions associated with PRG. Case Presentation A 63‐year‐old patient presented with a periapical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…With accurate assessment of the etiology of the defect, patient education, and a multidisciplinary approach, teeth with a palatal radicular may be retained with a stable outcome for years. 53,54 Many studies indicated that combined endodontic and periodontal therapy is required for successful healing of endo-perio lesions. 55,56 Schilder 57 postulated that either endodontic treatment or periodontal pathology will not produce favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…With accurate assessment of the etiology of the defect, patient education, and a multidisciplinary approach, teeth with a palatal radicular may be retained with a stable outcome for years. 53,54 Many studies indicated that combined endodontic and periodontal therapy is required for successful healing of endo-perio lesions. 55,56 Schilder 57 postulated that either endodontic treatment or periodontal pathology will not produce favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are shortterm cases dealing with these teeth in a multidisciplinary manner. 16 However, there is a dearth of case reports with long-term success. This case illustrates the advantages of saving a guarded tooth in the maxillary esthetic zone in a young patient with an apparent "hopeless" tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Teeth with a shallower groove and less depth of the groove down the root of the tooth have a better prognosis. There are short‐term cases dealing with these teeth in a multidisciplinary manner 16 . However, there is a dearth of case reports with long‐term success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors' knowledge, this is the first study analyzing this aspect. There have been several case reports demonstrating different approaches to treating these lesions [15][16][17][18][19]. Some showed success but only in a few patients and most of them referred only to single-rooted teeth.…”
Section: Discussionmentioning
confidence: 99%